Prevention of catheter-related infections by slver coated central venous catheters in oncological patients - Goldschmidt, Hartmut; Hahn, Uwe; Salwender, Hans; Haas, Rainer; Jansen, Bernd; Wolbring, Peter; Rinck, Michael; Hunstein, Werner (Zentralblatt für Bakteriologie, 1995)
Catheter-related infection (CRI) is a serious complication of central venous catheterization. We have investigated the efficacy of a silver-coated polyurethane catheter (Pellethane, Fresenius AG, Germany) in preventing CRI in oncological patients receiving chemotherapy in a phase II study. From November 1992 through April 1994, 266 patients were assigned to receive single lumen catheters, either standard uncoated catheters (UC, n = 113) or silvercoated ones (SC, n = 120). Catheters were inserted into the internal jugular vein after institutional approval and informed consent. Duration of catheterization (UC vs. SC = 13.3 vs. 12.7 days) and leukopenia (< 1.0 x 109 WBC/1; 4.3 vs. 3.6 days) were similar in both groups demonstrating a comparable risk for infections. Skin reactions at the catheter entry site were recorded daily. CRI and colonization rates were studied by semiquantitatively culturing intradermal and intravascular segments. CRI were confirmed by blood cultures obtained via catheter and from peripheral veins in cases of suspected sepsis or at the end of catheterization. No adverse effects from the silver-coated catheter could be observed. The bacteriological results showed that SC were colonized (> 15 CFU) in 45.1 % and UC in 44.2 %. CRI developed in 21.2% of the UC patients but only in 10.2% of the SC patients (p = 0.011). We conclude that this new silver-coated central venous catheter is biocompatible and effective in reducing the incidence of catheter-related infections in oncological patients.
Elektronische Reproduktion der Druck-Ausgabe 8. November 2011
Gesehen am 12.05.2025